2013
DOI: 10.1371/journal.pone.0064151
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Detergent-Decellularized Equine Tendon Extracellular Matrix for Tissue Engineering Applications

Abstract: Natural extracellular matrix provides a number of distinct advantages for engineering replacement orthopedic tissue due to its intrinsic functional properties. The goal of this study was to optimize a biologically derived scaffold for tendon tissue engineering using equine flexor digitorum superficialis tendons. We investigated changes in scaffold composition and ultrastructure in response to several mechanical, detergent and enzymatic decellularization protocols using microscopic techniques and a panel of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 56 publications
2
89
1
Order By: Relevance
“…Other research also showed that MSCs reseeded on 2% SDS-treated equine tendon ECM were successful in terms of plating efficiency, cell proliferation, and viability. 46 Therefore, the recellularization ability of ECM scaffolds derived from fibroblast cell sheets is independent of decellularization methods and the amount of cellular remnants in our study.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Other research also showed that MSCs reseeded on 2% SDS-treated equine tendon ECM were successful in terms of plating efficiency, cell proliferation, and viability. 46 Therefore, the recellularization ability of ECM scaffolds derived from fibroblast cell sheets is independent of decellularization methods and the amount of cellular remnants in our study.…”
mentioning
confidence: 61%
“…The hMSCs are often employed as a model cell line to evaluate the feasibility of using decellularized scaffolds for tissue engineering, 46 because hMSCs have wide applications in bone, tendon, skin, vascular, and neural tissue engineering. It was reported that when SDS was added to the decellularization protocol, the ability of porcine dermis to support in vitro cell growth significantly decreased due to the harsh effect of SDS.…”
mentioning
confidence: 99%
“…We found that MSCs adhered to and elongated on fibrous scaffolds of both parallel and perpendicular oriented fibers, maintained viability, and migrated along both individual and multiple fibers regardless of fiber orientation. Previous studies using aligned fibrous scaffolds have shown that MSCs elongate along aligned fibrous scaffolds to promote tenocyte-like morphologies and tendon differentiation, while random electrospun fibrous scaffolds promote polygonal cell morphology and random cell orientation [16,31,32]. Instead of randomly oriented fibers, we used aligned perpendicular fibers resulting in primarily two different morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…Decellularization may be accomplished by acid, detergent, enzymatic, and mechanical methods, all of which can affect the biochemical and structural characteristics [47][48][49] ( Fig. 4).…”
Section: Decellularized Ecmmentioning
confidence: 99%